Parkia biglobosa (Nere)-A threatened useful tree species: Directory of sanitary constraints according to north-south climatic gradient in Mali - Kelly, Bokary Allaye; Kouyaté, Amadou Malé (Current Botany, 2020)
Parkia biglobosa, a multi-purposes species offers food, medicine and income to rural populations. This species is facing several constraints mainly aged populations, weak natural regeneration, and reduction of tree densities. A study, was undertaken in three sites from three agro-climatic zones according to the north-south climatic gradient in southern Mali, to assess dendrometric characteristics of Parkia biglobosa trees. Permanent plots of 0.25 ha each were installed in fields and fallows with three replications in each stand within each site. Adult trees in the plots were monitored, measured and also assessed for sanitary constraints. Several sanitary constraints were encountered and classified into six categories (from attacks on trunks and gross branches to damages on fruits and general attacks, infestations and damages due to wood-boring insects, human beings and other abiotic factors). Damages like those with symptoms of dieback or staghead disease pose a serious threat for production, productivity and survival of the species. Concrete actions are necessary like sanitary diagnostic at the level of the distribution area of the species in Mali, followed by identifying real cause of damages and seeking for appropriate solutions, sensitizing and training farmers, implementing a national program of regeneration of the species by planting and/or by promoting Assisted Natural Regeneration (ANR) approach.